1966
DOI: 10.1017/s0021859600062663
|View full text |Cite
|
Sign up to set email alerts
|

Studies in potato agronomy. II. The effects of variety and time of planting on growth, development and yield

Abstract: 1. A factori al experiment involving four varieties (Ulster Chieftain, Arran Pilot, Craig's Royal and Ulster Torch) and three times of planting (28 March, 13 April and 2 May) was undertaken with a view to investigating the effects on growth development and yield of these factors. Only a limited amount of data was obtained in respect of Craig's Royal, because of its extreme variability in the first two times of planting. In addition, data in respect of King Edward and Majestic planted on the second date in an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

1974
1974
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 5 publications
(7 reference statements)
3
13
1
Order By: Relevance
“…The same was observed for the cultivars. These results contrast with the observations made by Milthorpe (1963), Ivins & Bremner (1965), Bremner & Radley (1966) and Ewing & Struik (1992), based on a limited number of cultivars, on the determinant influence of tuber initiation on the development of the potato plant. Ivins & Bremner (1965) and Slater (1963) indicated that the rate of tuber growth and the time to foliage senescence were related to the size of the canopy present at tuber initiation.…”
Section: Discussioncontrasting
confidence: 99%
“…The same was observed for the cultivars. These results contrast with the observations made by Milthorpe (1963), Ivins & Bremner (1965), Bremner & Radley (1966) and Ewing & Struik (1992), based on a limited number of cultivars, on the determinant influence of tuber initiation on the development of the potato plant. Ivins & Bremner (1965) and Slater (1963) indicated that the rate of tuber growth and the time to foliage senescence were related to the size of the canopy present at tuber initiation.…”
Section: Discussioncontrasting
confidence: 99%
“…Tuber fresh yield is closely related to leaf area duration (Bremner and Radley, 1966;. The shortening of the growing period was the main cause of the lower tuber yield with the later planting date in this study.…”
Section: Discussionmentioning
confidence: 46%
“…3). Also, tuber initiation makes diversion of assimilates to tuber, thus early tuber initiations cause small plants and leaf area leading to lower final yield (Ivins and Bremner, 1965;Bremner and Radley, 1966). Therefore, environmental conditions during the early growth (before tuber initiation and early tuber growth phase) may play crucial role for the late tuber growth.…”
Section: Discussionmentioning
confidence: 99%